Assessment of tertiary reed beds in chemically-dosed wastewater treatment plants for phosphorus removal - Prieto Fort, Raul (Cranfield University, 2013)
Eutrophication is one of the problems affecting the environmental quality standards of fresh waters. Phosphorus (P) is considered a main nutrient contributing to this. In the UK, the Water Industry is responsible for c. 50% of the total phosphorus load to freshwater ecosystems. Within this, small wastewater treatment plants (WwTPs) (<2,000 population equivalent) have a significant role since they represent 75% of all WwTPs in the UK. The current option for P removal from wastewater is chemical precipitation through the dosing of iron (Fe) salts in combination with a tertiary filtration treatment step. This study aims to determine the transformation processes whereby tertiary reed beds permanently store or release iron and phosphorus in chemically-dosed sites to provide recommendations regarding the conditions where reed beds can be used as such final filtration treatment in small WwTPs. This was carried out through sampling campaigns in 14 full-scale tertiary reed beds. Chemically-dosed WwTPs with tertiary reed beds can perform satisfactorily achieving phosphorus removals above 85% and average P and Fe final effluent concentrations of 0.7 mg P/L and 0.2 mg Fe/L, respectively, both well below consents (2 mg TP/L and 4 mg Fe/L). The majority of the total phosphorus in the reed bed influents was associated to either suspended solids or dissolved fractions, whereas 60¬90% of the effluent TP is in the dissolved form. Occasional episodes of phosphorus release from the reed bed can occur, as evidenced in an increase in soluble reactive phosphorus in the effluent. The main mechanism for trapping of Fe and P in mature beds was settlement of suspended particles, with phosphorus and iron concentrations in the accumulated sludge being up to 55.9 g P/kg dry matter and 246.6 g Fe/kg DM. The removal of particulate pollutants was successful in the reed beds studied, but colloidal and dissolved particles passing through the beds untreated. This could compromise the use of reed beds with future tightening P consents if the current chemical dosing practices are unchanged.